Immune Control of Legionella Infection: An in vivo Perspective - Schuelein, Ralf; Ang, Desmond; van Driel, Ian R.; Hartland, Elizabeth L. (Frontiers in Microbiology, 2011)
Legionella pneumophila is an intracellular pathogen that replicates within alveolar macrophages. Through its ability to activate multiple host innate immune components, L. pneumophila has emerged as a useful tool to dissect inflammatory signalling pathways in macrophages. However the resolution of L. pneumophila infection requires multiple cell types and abundant cross talk between immune cells. Few studies have examined the coordination of events that lead to effective immune control of the pathogen. Here we discuss what is known about L. pneumophila interactions with macrophages and dendritic cell subsets and highlight the paucity of knowledge around how these interactions recruit and activate other immune effector cells in the lung.